Kecerdasan Emosional dan Motivasi Serta Dampaknya Terhadap Kinerja Pegawai Negeri Sipil - Inas Maulana Cahya Werdhi (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
This study discusses human resources regarding emotional intelligence and motivation for employee performance. The number of samples was 55 with the status of Civil Servants (PNS) and This study aims to prove whether there is a influence between the independent variable on the dependent variable. Researcher are interested in taking topics related to emotional intelligence for each employee, where emotional intelligence plays an important role in determining attitudes and managing emotions at work and achieving company goals and individual achievements. The analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression tests, R2 tests, t tests and F tests. simultaneous namely emotional intelligence (X1) and motivation (X1) there is an influence on employee performance. Based on the results of the simultaneous regression analysis, the Fcount value was 34.994 with a significance F 0.000 <0.05. In the simultaneous or joint test, the three variables of emotional intelligence, motivation and performance have a joint influence. Meanwhile, partially emotional intelligence (X1) has an influence on performance (Y) and motivation (X2) has an influence on performance (Y). Based on these results, it shows that employees can show that they have achievements in their field of work. Not only work but can show integrity in himself, and can increase work motivation.